Professional responsibilities of the economics teachers - TASCOVICI, Daliana Ecaterina; DRAGOMIR, Robert Gabriel (Annals of Spiru Haret University. Economic Series, 2011)
The present paper’s aim is to present the professional responsibilities belonging to teachers of economics. Firstly, we mentioned the mixed investigations addressed to the teachers activities: pedagogical, psychological, social and axiological. Secondly we define the expectancies concerning the teachers’ knowledge, abilities and attitudes in the present day’s environment learning. In order to establish these issues, we identified the needs of the education system. Here we present the actual points of view, advised pedagogical opinions, stages of the research in this field. Within the last part of the paper, we established the responsibilities for the teachers; expectancies under the form of enunciations for the following five activity domains: instruction, evaluation, learning environment, human relations and professional engagement, at the same time taking into account the three dimensions: knowledge, abilities and attitudes.